Analisis Etika Profesi Hakim Mahkamah Konstitusi terhadap Dampak Pelanggaran Kode Etik dalam Putusan MK Nomor 90/PUU-XXI/2023 - Amanda, Niken Dwi; Azzahra, Fidda Nazli; Nurdin, Merry Kurniawati; Dharmawan, Cinta Rizqareka; Rahmadani, Novia; Rachman, Rheyna Reva; Az Zahra, Hilyah; Ardyanti, Widyarini; M, Mulyadi (Media Hukum Indonesia (MHI), 2025)
The Constitutional Court (Mahkamah Konstitusi) plays a crucial role in safeguarding the constitution and upholding the principles of constitutional democracy in Indonesia. However, its credibility and integrity have been seriously questioned following the issuance of Constitutional Court Decision No. 90/PUU-XXI/2023, which addresses the minimum age requirement for presidential and vice-presidential candidates. This ruling sparked widespread controversy due to its perceived political interests and alleged violations of judicial ethics by several justices, particularly Chief Justice Anwar Usman, who was found by the Constitutional Court’s Honorary Council (MKMK) to have breached impartiality due to a family conflict of interest involving one of the candidates favored by the decision. This study employs a normative legal research method using both statutory and conceptual approaches to critically analyze the role of judicial ethics in maintaining the independence of the Constitutional Court, and to evaluate the legal and sociological implications of ethical violations on the legitimacy and validity of the Court's decision. The analysis shows that while the ruling remains legally valid and binding in accordance with Article 24C of the 1945 Constitution and the Constitutional Court Law (UU MK), which affirms the final and binding nature of Constitutional Court decisions, its moral and social legitimacy is significantly undermined due to unethical practices that contradict the principles of integrity, transparency, and accountability. Ethical violations in the decision-making process not only tarnish the personal reputation of the justices involved but also erode public trust in the institutional independence of the Constitutional Court. In modern constitutional legal systems, procedural legality cannot be separated from constitutional morality. The continued function of the Constitutional Court as the protector of citizens' constitutional rights and the guardian of constitutional supremacy is heavily dependent on the legitimacy derived from public trust. Therefore, reforming the judicial ethics system and strengthening the role of the MK as an independent and effective ethical oversight body is an urgent necessity to ensure that the Constitutional Court remains a dignified and authoritative institution in Indonesia's constitutional democrac